The Role of Fear of Missing Out (FOMO) and Hedonic Lifestyle in Shaping Students' Personal Financial Management: The Moderating Effect of Self-Control - Ula Lambang Trisnoprinia Putra; Ida Nur Aeni (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Personal financial management is essential for university students to achieve financial well-being, yet psychological factors such as Fear of Missing Out (FOMO) and a Hedonic Lifestyle may influence their financial behavior. This study aims to examine the influence of Fear of Missing Out (FOMO) and a Hedonic Lifestyle on students' personal financial management and to test the role of self-control as a moderating variable. The research uses a descriptive quantitative approach with a population of 170 Accounting Education students. The sample was determined using the Slovin formula with a 5% error rate, resulting in 120 respondents. Data were collected through an online questionnaire and analyzed using multiple linear regression and Moderated Regression Analysis (MRA) in IBM SPSS Statistics. The findings showed that FOMO did not significantly affect students' personal financial management, whereas a Hedonic Lifestyle had a significant positive effect. Simultaneously, FOMO and Hedonic Lifestyle did not significantly affect personal financial management. The MRA results indicated that self-control had a significant direct effect but did not moderate the effects of FOMO and Hedonic Lifestyle. These findings imply that financial management is more strongly influenced by financial knowledge and planning skills than by psychological factors. Therefore, universities should strengthen practical financial education emphasizing budgeting, financial planning, and responsible spending habits.